Aquatic ecosystem functions of an isolated floodplain and their implications for flood retention and management. Issue 1 (21st December 2012) - Reckendorfer, Walter; Funk, Andrea; Gschöpf, Christine; Hein, Thomas; Schiemer, Fritz; Arnott, Shelley
Summary We used an isolated floodplain of the river Danube as a model system to gain an understanding on the functioning of retention areas to predict future developments and to sustain their ecological services. We applied correlation analysis and spline regression models to assess the effects of geomorphology, hydraulics, and seasonality on sediment characteristics, suspended solids, hydrochemistry and primary producers. The spatio‐temporal connection to the river is the primary factor influencing the hydrochemical characteristics and sediments. Allochthonous processes such as nutrient and sediment input during high waters dominate in connected parts of the floodplain, whereas autochthonous processes, for example, the release of phosphorus from the sediments and internally driven eutrophication, dominate in isolated parts. These conditions also affect the dominating primary producers, biodiversity, the degree of floodplain aggradation and thus the potential life span of aquatic habitats. Measures to improve the functional basis for ecological services may use both allochthonous and autochthonous processes as a starting point, that is, minimizing sediment storage and nutrient input and improving the water balance to prolong the life span of isolated waters, and thus maximizing water body diversity and associated biodiversity. Based on the results of our analysis and literature, eight alternative management measures have been evaluated. As a result, we propose a stepwise adaptive approach beginning with a controlled water supply with low sediments and nutrient loads. If these measures prove insufficient to sustain ecological functions and conservation value, more radical steps must be considered. Synthesis and applications The increasing problems with catastrophic flooding have forced decision makers to seek basin‐wide solutions with focus on 'more room for the river' and the reintegration of former floodplains as retention basins. Such reintegrations also represent opportunities to improve the ecological conditions for nature development in addition to their principal function, that is, the storage of water during floods. The results of our study can serve as an effective tool to predict the effects of alternative management options and to establish and define the design criteria of water retention areas with regard to their ecological functions, life spans and biodiversity.